2011
DOI: 10.2190/pm.41.4.f
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorders, Hypertension, and Cardiovascular Risk: A Review

Abstract: Hypertension, coronary heart disease (CHD), and anxiety disorders all cause substantial morbidity to patients and costs to the healthcare system. Associations between these diseases have been hypothesized and studied for decades. In particular, psychosocial stressors associated with anxiety disorders raise autonomic arousal via the hypothalamic-pituitary axis which increases circulating catecholamines. This heightened arousal is associated with an increased risk of hypertension and a pro-inflammatory state and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
2
15

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 76 publications
3
130
2
15
Order By: Relevance
“…Hypertension is part of a cardiovascular risk profile. Significant bidirectional associations between hypertension and psychosocial risk factors have been observed, although there is considerable heterogeneity between different studies, and an absence of associations has been observed as well [30][31][32]. Overall, the present findings do not confirm a strong effect of hypertension as part of a cardiac risk profile, on the association between PE and long-term psychosocial distress.…”
Section: Discussioncontrasting
confidence: 82%
“…Hypertension is part of a cardiovascular risk profile. Significant bidirectional associations between hypertension and psychosocial risk factors have been observed, although there is considerable heterogeneity between different studies, and an absence of associations has been observed as well [30][31][32]. Overall, the present findings do not confirm a strong effect of hypertension as part of a cardiac risk profile, on the association between PE and long-term psychosocial distress.…”
Section: Discussioncontrasting
confidence: 82%
“…Anxiety is characterized by symptoms such as palpitations, sweating, trembling or shaking, shortness of breath or smothering sensations, chest pain or discomfort, and/or stomach distress (6) . Anxiety activates the sympathetic nervous system leading to a variety of physiological responses (7) , such as tachycardia, sweating, increased oxygen consumption, hypertension, which can worsen the evolution of the patient. In addition, anxiety can have a negative effect on a patient's clinical outcomes such as treatment refusal and reduced tolerance to pain before, during and after the catheterization intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Te spremembe pa vodijo do tromboze koronarnih arterij prek hemodinamskih učinkov na aterosklerotične plake ali aktiviranja protrombogenih faktorjev in de novo tromboze (47). Aktivirata živčno-hormonski sistem, hipotalamično-hipofizno-adrenalno os (HHA-os) in simpatični živč-ni sistem, ki imata sistemske in lokalne učinke (47)(48)(49). Zaradi vazokonstrikcije se poviša krvni pritisk, pospeši se prevajanje iz sinusnega vozla in poviša frekvenca srca (47)(48)(49).…”
Section: Potencialni Mehanizmiunclassified
“…Aktivirata živčno-hormonski sistem, hipotalamično-hipofizno-adrenalno os (HHA-os) in simpatični živč-ni sistem, ki imata sistemske in lokalne učinke (47)(48)(49). Zaradi vazokonstrikcije se poviša krvni pritisk, pospeši se prevajanje iz sinusnega vozla in poviša frekvenca srca (47)(48)(49). Ob tem se poveča delo in poraba kisika v srčni mišici, kar lahko vodi do raztrganosti plaka (47)(48)(49).…”
Section: Potencialni Mehanizmiunclassified
See 1 more Smart Citation